Crack layer model for semi-elliptical surface cracks in HDPE pipes and application in buried pipes with complicated loading conditions. (15th October 2021) - Wee, Jung-Wook; Chudnovsky, Alexander; Choi, Byoung-Ho
Highlights: Kinetics of a semi-elliptical surface crack layer of polyethylene pipe was modeled for the first time. Effect of complicated loading on the structural integrity of a buried pipe was analytically studied. The lifetime of a buried pipe with complicated loading condition was analytically investigated. Abstract: The crack layer (CL) model can be used to theoretically simulate unique discontinuous slow crack growth (SCG) and the consequent lifetime of pipe-grade high-density polyethylene (HDPE). However, its application has been limited to several specimen configurations and 1-dimensional (1D) crack growth in pipes. In this study, a 2-dimensional (2D) CL growth model was formulated for a semi-elliptical surface crack in an HDPE pipe, for the first time. The 2D semi-elliptical discontinuous SCG kinetics of the inner surface of the pipe were successfully simulated. In addition, the proposed model was applied to a buried HDPE pipe under the complicated loading condition, e.g., internal pressure, ground pressure induced by structures and traffic loads, as well as the point load due to stones contacting the pipe surface. As the point load exerted by such hard objects within the soil medium can reduce the structural integrity of the buried pipes, this effect is a valid consideration. Various levels of these loading conditions were applied for semi-elliptical CL growth simulations, with different stone sizes in contact with the buried pipe. The results indicate that the diameter of the stone influences semi-elliptical crack propagation behavior and significantly reduces failure time even under the same external loading condition. In addition, it was observed that the lifetime reduction rate depends on the ratio of the internal pressure to ground pressure. This study broadens the applicability of the 2D CL model for buried HDPE pipes to more practical situations and quantifies the effect of stone-embedded soils on SCG kinetics and its lifetime. Graphical abstract: Image, graphical abstract